Depressive disorders and quality of live in patients with acute coronary syndrome in real clinical practice - E. V. Konstantinova; E. A. Koroleva; A. G. Popova; E. E. Popov; D. A. Anichkov; A. V. Svet; A. P. Nesterov; M. Yu. Gilyarov (Klinicist)
Objective. To study the prevalence of depressive disorders using Zung Self-rating Depression Scale (SDS) in patients with acute coronary syndrome (ACS) in the daily work of the Regional Vascular Center in various gender and social subgroups and to compare their severity with the life quality level.Materials and Methods. The survey included 116 (57 female and 59 male) patients, admitted to Regional Vascular Center with ACS from March to November 2020 (Group 1), and 49 patients hospitalized with other cardiological pathology (Group 2), who made up a comparison group comparable in gender, age, presence of diabetes mellitus, heart attack and stroke in anamnesis.Results. In Group I the score on SDS was higher or equal to 50 (depression) in 18 % of cases: 15 % female and 3 % male patients (p <0.05). The average score on SDS was notably higher in women than in men (p <0.05). In Group 2 depression was detected in 27 % of cases, without gender differences. The average level of depression was higher in older age groups, both in men and women, in patients with ACS and without ACS. A negative correlation was established for the indicators of SDS and SF-36: in Group 1 r = –0.62, p <0.05, in Group 2 r = –0.76, p <0.05. In Group 1 indicators of health physical component (SF-36) among women were: physical functioning 50, role functioning 34, general health 51, in men: 80, 58 and 63 respectively (p <0.05). In Group 2 these indicators significantly differed only in physical functioning: 60 female and 72 male. In Group 1 depression was observed in 2 % of working and in 30 % of non-working patients (p <0.05); in Group 2: 0 and 34 % respectively. In Groups 1 and 2 depression was found in 10 and 5 % among married, in 31 and 43 % among unmarried patients (p <0.05). In Group 1 depression was detected in 31 % among patients with diabetes, in 12 % – without diabetes (p <0.05). The other analyzed diseases did not have a significant effect on the de pression score.Conclusions. The presence of ACS was associated with depressive disorders in women. At the same time, the severity of depressive disorders was inversely correlated with the quality of life. In women with ACS, the physical component and the psychological component of health on the quality of life scale are significantly lower in comparison with men. In addition, the absence of work and marriage negatively affected the prevalence of depressive disorders among all examined patients. And the presence of diabetes mellitus was associated with a higher level of depression among patients with ACS. It is necessary to develop and implement specialized rehabilitation programs for the following subgroups of patients with ACS and depression – unemployed and unmarried women, with a low level of quality of life, elderly patients, patients with diabetes mellitus.